Optimalisasi Penggunaan Instagram untuk Meningkatkan Reputasi Positif Polri melalui Media Sosial - Tiani, Alni; Setyanto, Yugih (Kiwari, 2024)
This research aims to explore effective advertising strategies via Instagram to increase the positive image of the National Police. The focus of this research is on the Central Jakarta Police Criminal Investigation Unit as an important representation of the Indonesian National Police (Polri). The main objective of the research is to evaluate the strategy for using the Instagram platform by the Criminal Investigation Unit in forming and maintaining a positive image of the National Police in the eyes of the public. The methodology used includes a qualitative approach with a case study approach, involving members and managers of Instagram accounts, as well as their followers. Research findings reflect a variety of social media utilization strategies, from content types to active interactions with followers. It is hoped that the results of this research will provide in-depth insight regarding the effectiveness of Polri's communication efforts via Instagram, as well as its positive contribution in designing institutional communication strategies in the future. These findings also provide a foundation for a deeper understanding of how police agencies can be relevant. Penelitian ini bertujuan untuk mengeksplorasi strategi advertising yang efektif melalui Instagram guna meningkatkan citra positif Polri. Fokus penelitian ini tertuju pada Satuan Reserse Kriminal Polres Jakarta Pusat sebagai representasi penting dari Kepolisian Republik Indonesia (Polri). Tujuan utama penelitian adalah untuk mengevaluasi strategi pemanfaatan platform Instagram oleh Satuan Reserse Kriminal dalam membentuk dan memelihara citra positif Polri di mata masyarakat. Metodologi yang digunakan mencakup pendekatan kualitatif dengan pendekatan studi kasus, melibatkan anggota dan pengelola akun Instagram, serta pengikutnya. Temuan penelitian mencerminkan beragam strategi pemanfaatan media sosial, dari jenis konten hingga interaksi aktif dengan pengikut. Hasil penelitian ini diharapkan dapat memberikan wawasan mendalam terkait efektivitas upaya komunikasi Polri melalui Instagram, serta kontribusi positifnya dalam perancangan strategi komunikasi institusional di masa depan. Temuan ini juga menjadi landasan bagi pemahaman lebih mendalam tentang cara lembaga kepolisian dapat secara relevan.